TOXICIDADE DE EXTRATOS AQUOSOS DAS FOLHAS DE Campomanesia sessiliflora e Campomanesia guazumifolia em Artemia salina - CASTRO, Thiago Luis Aguayo de; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2020)
-